Bicontinuous eutectic electrolyte and preparation method and application thereof
By using dual continuous eutectic electrolyte in lithium-ion batteries and using the combination of deep eutectic electrolyte and polymer monomer to form a microscopic bicontinuous phase separation structure, the problem of insufficient long cycle stability of lithium-ion batteries is solved, and the problem of insufficient lithium-ion batteries is achieved Highly efficient ion conduction and mechanical support significantly improve the electrochemical performance and safety performance of the battery.
Patent Information
- Application Number
- CN202411583272.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-11
AI Technical Summary
The long cycle stability of existing lithium-ion batteries is insufficient, especially when using deep eutectic electrolyte-polymer systems, there is room for improvement in electrochemical performance and safety performance.
The double continuous eutectic electrolyte is adopted, which consists of deep eutectic electrolyte, polymer monomer, crosslinking agent and initiator. Through in situ radical polymerization, it forms a microscopic bicontinuous phase separation structure, enriches the deep eutectic electrolyte in Ion phase region to improve ion conduction and mechanical properties.
It achieves excellent long-cycle stability of lithium-ion batteries, with low interface impedance, high ion conductivity, stable decomposition voltage, high capacity retention and high Coulomb efficiency, significantly improving the electrochemical performance and safety performance of the battery.
Smart Images

Figure CN119419352A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of eutectic electrolytes, and in particular to a bicontinuous eutectic electrolyte and a preparation method and application thereof. Background Art
[0002] In recent years, lithium-ion batteries have been widely used in power vehicles and electronic products. The high energy density and high safety performance of lithium-ion batteries are difficult to be compatible, resulting in many catastrophic accidents. Traditional lithium-ion batteries mainly use organic liquid electrolytes, which have safety risks such as electrolyte leakage and combustion. In addition, the energy density of traditional lithium-ion batteries based on graphite negative electrodes has approached its theoretical limit. The growing demand for high-energy-density lithium-ion batteries has prompted the use of lithium metal negative electrodes with the lowest electrochemical potential (-3.04Vvs standard hydrogen electrode) and the highest theoretical specific capacity (3860mAh / g). The use of lithium metal exacerbates the already serious safety issues. Lithium dendrites formed during the electrochemical lithium deposition and stripping process may penetrate the diaphragm, causing short circuits and thermal runaway in the battery, and ultimately leading to fires and tragedies. In response to the development needs of high-safety and high-specific-energy secondary batteries, it is urgent to develop new electrolytes with high safety and stability.
[0003] Deep eutectic, also known as deep eutectic solvent (DES), refers to two or more substances mixed in a certain proportion. Due to molecular interactions such as hydrogen bonds, the melting point of the mixture is reduced and it presents a solution state. Among the many deep eutectic solvents, some are composed of electrolyte salts as ligands, so they have ion conductivity properties corresponding to their electrolyte salt ligands. Therefore, this type of deep eutectic solvent with ion transfer function is also called deep eutectic electrolyte (DEE). Deep eutectic electrolytes have the advantages of easy preparation, low cost, promotion of ion dissociation, and higher safety relative to carbonate solvents. They have begun to be used in electrolyte materials and are considered to be a potential emerging electrolyte.
[0004] Researchers have carried out some work to promote the further application of deep eutectic electrolytes. The prior art discloses an amide-based deep eutectic electrolyte, which exhibits good compatibility with lithium metal negative electrodes, high stability, and the ability to promote lithium ion dissociation. The prior art constructs a new solid-state polymer electrolyte with a wide electrochemical stability window and high ion conductivity by adding a lithium salt-based deep eutectic electrolyte to a PEO-based cross-linked network. However, the long-cycle stability of batteries using the above-obtained deep eutectic electrolyte-polymer system needs to be further improved. Summary of the invention
[0005] In view of this, the object of the present invention is to provide a bicontinuous eutectic electrolyte and a preparation method and application thereof. The battery using the bicontinuous eutectic electrolyte provided by the present invention has excellent long-cycle stability.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a bicontinuous eutectic electrolyte, the preparation raw materials of which include: a deep eutectic electrolyte, a polymer monomer, a cross-linking agent and an initiator;
[0008] The polymer monomers are at least two of 2,2,2-trifluoroethyl acrylate, 2-(perfluorobutyl)ethyl methacrylate and perfluorohexylethyl acrylate;
[0009] The bicontinuous eutectic electrolyte has a microscopic bicontinuous phase separation structure.
[0010] Preferably, the phase separation size in the microscopic bicontinuous phase separation structure is 10 nm to 10 μm.
[0011] Preferably, the deep eutectic electrolyte is prepared by eutecticization of a ligand and an electrolyte salt, the molar ratio of the ligand to the electrolyte salt is 2:1 to 8:1; the ligand is an amide or a sulfone; and the electrolyte salt is lithium bis(trifluoromethanesulfonyl)imide.
[0012] Preferably, the amide includes one or more of 1,3-dimethyl-2-imidazolidinone, N-methylacetamide, N-methyl-2,2,2-trifluoroacetamide and N-methylurea, and the sulfone includes one or more of dimethyl sulfone, dibutyl sulfone and cyclopentane sulfone.
[0013] Preferably, the crosslinking agent is poly(ethylene glycol) diacrylate, and the amount of the crosslinking agent is 0.2-5% of the amount of the polymer monomer.
[0014] Preferably, the initiator comprises azobisisobutyronitrile and / or dibenzoyl peroxide; the mass of the initiator and the total volume of the deep eutectic electrolyte and the polymer monomer are in a ratio of 0.1 to 1 mg / mL.
[0015] Preferably, based on the total volume of the deep eutectic electrolyte and the polymer monomer being 100%, the volume content of the polymer monomer is 10-60%.
[0016] The present invention also provides a method for preparing the bicontinuous eutectic electrolyte described in the above technical solution, comprising the following steps:
[0017] mixing a polymer monomer and a cross-linking agent to obtain a polymer precursor solution;
[0018] dissolving the initiator with a portion of the deep eutectic electrolyte to obtain an initiator solution;
[0019] During the battery assembly process, the polymer precursor solution, the initiator solution and the remaining deep eutectic electrolyte are mixed, and in-situ free radical polymerization is carried out under thermal initiation conditions to obtain the bicontinuous eutectic electrolyte.
[0020] Preferably, the temperature of the in-situ free radical polymerization is 40-100° C., and the time is 2-30 hours.
[0021] The present invention also provides the use of the bicontinuous eutectic electrolyte described in the above technical solution or the bicontinuous eutectic electrolyte prepared by the preparation method described in the above technical solution in a lithium ion battery.
[0022] The invention provides a bicontinuous eutectic electrolyte.
[0023] The bicontinuous eutectic electrolyte provided by the present invention combines the advantages of deep eutectic electrolyte with the advantageous phase structure of bicontinuous phase separation structure (mechanical phase region and ionic phase region), and while forming a microscopic bicontinuous phase separation structure, enriches the deep eutectic electrolyte in the ionic phase region of the bicontinuous phase separation structure, and finally constructs a new bicontinuous eutectic electrolyte. In the bicontinuous eutectic electrolyte of the present invention, the ionic phase region (deep eutectic electrolyte) can achieve efficient ion transport, and the mechanical phase region can ensure sufficient mechanical support; therefore, the bicontinuous eutectic electrolyte of the present invention can achieve a synergistic improvement in ion conductivity and mechanical properties, thereby improving the electrochemical properties and safety performance of lithium-ion batteries, and the macroscopic manifestation is that the bicontinuous eutectic electrolyte has long cycle stability. At the same time, the present invention uses at least two of 2,2,2-trifluoroethyl acrylate, 2-(perfluorobutyl) ethyl methacrylate and perfluorohexyl ethyl acrylate as polymer monomers, so that the bicontinuous eutectic electrolyte has a high fluorine content, so that the battery using the bicontinuous eutectic electrolyte has excellent long cycle stability.
[0024] The data of the embodiment show that the interface impedance of the bicontinuous eutectic electrolyte of the present invention is 120-210Ω at room temperature; the ionic conductivity at room temperature is 1.42×10 -4 S / cm~2.52×10 -4 S / cm; decomposition voltage is 4.3~4.7V; at current density of 0.1mA / cm -2 It can stably cycle for more than 400 times; after 2500 cycles, the capacity retention rate exceeds 70% and the Coulomb efficiency is >99%.
[0025] The present invention also provides a method for preparing the bicontinuous eutectic electrolyte described in the above technical solution. The preparation method provided by the present invention is simple to operate, has strong universality, is low in cost, and has prospects for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the bicontinuous eutectic electrolyte obtained in Example 1;
[0027] Figure 2 The AC impedance diagram of the bicontinuous eutectic electrolyte obtained in Example 1 at different temperatures;
[0028] Figure 3 Graph showing the ionic conductivity of the bicontinuous eutectic electrolyte obtained in Example 1;
[0029] Figure 4 : LSV curve of the bicontinuous eutectic electrolyte obtained in Example 1;
[0030] Figure 5 This is a long cycle stability diagram of the Li / / Li symmetric battery with the bicontinuous eutectic electrolyte obtained in Example 1;
[0031] Figure 6 This is a performance diagram of a lithium metal battery with a bicontinuous eutectic electrolyte obtained in Example 1. DETAILED DESCRIPTION
[0032] The present invention provides a bicontinuous eutectic electrolyte, the preparation raw materials of which include: a deep eutectic electrolyte, a polymer monomer, a cross-linking agent and an initiator;
[0033] The polymer monomers are at least two of 2,2,2-trifluoroethyl acrylate, 2-(perfluorobutyl)ethyl methacrylate and perfluorohexylethyl acrylate;
[0034] The bicontinuous eutectic electrolyte has a microscopic bicontinuous phase separation structure.
[0035] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0036] In the present invention, the bicontinuous eutectic electrolyte has a microscopic bicontinuous phase separation structure, and the phase separation size in the microscopic bicontinuous phase separation structure is preferably 10 nm to 10 μm.
[0037] The raw materials for preparing the bicontinuous eutectic electrolyte provided by the present invention include a deep eutectic electrolyte, and the deep eutectic electrolyte is preferably prepared by eutecticization of a ligand and an electrolyte salt; the ratio of the amount of matter of the ligand and the electrolyte salt is preferably 2:1 to 8:1, more preferably 4:1 to 6:1, specifically 2:1, 3:1, 4:1, 5:1, 6:1, 7:1 or 8:1. In the present invention, the ligand is preferably an amide or a sulfone. In the present invention, the amide preferably includes one or more of 1,3-dimethyl-2-imidazolidinone, N-methylacetamide, N-methyl-2,2,2-trifluoroacetamide and N-methylurea. In the present invention, the sulfone preferably includes one or more of dimethyl sulfone, dibutyl sulfone and cyclopentane sulfone. In the present invention, the electrolyte salt is preferably lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). In the present invention, the preparation method of the deep eutectic electrolyte preferably includes the following steps: mixing the ligand and the electrolyte salt, eutecticizing, and obtaining the deep eutectic electrolyte; the eutectic temperature is preferably 20-60°C, more preferably 40-50°C, specifically 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C or 60°C; the present invention does not specifically limit the time of the eutectic, as long as all the solid substances are converted into liquid substances. In the present invention, the eutectic is preferably carried out under a nitrogen atmosphere, and the contents of water vapor and oxygen in the nitrogen atmosphere are preferably independently <0.1ppm; the eutectic is preferably carried out in a glove box.
[0038] The raw materials for preparing the bicontinuous eutectic electrolyte provided by the present invention include polymer monomers, and the polymer monomers are at least two of 2,2,2-trifluoroethyl acrylate, 2-(perfluorobutyl)ethyl methacrylate and perfluorohexylethyl acrylate, preferably a mixture of 2,2,2-trifluoroethyl acrylate and 2-(perfluorobutyl)ethyl methacrylate, a mixture of 2,2,2-trifluoroethyl acrylate and perfluorohexylethyl acrylate, a mixture of 2,2,2-trifluoroethyl acrylate and 2-(perfluorobutyl)ethyl methacrylate and perfluorohexylethyl acrylate, and further preferably a mixture of 2,2,2-trifluoroethyl acrylate and 2-(perfluorobutyl)ethyl methacrylate. In the present invention, the molar ratio of 2,2,2-trifluoroethyl acrylate and 2-(perfluorobutyl)ethyl methacrylate in the mixture of 2,2,2-trifluoroethyl acrylate and 2-(perfluorobutyl)ethyl methacrylate is preferably 1:1 to 1:4, more preferably 1:1, specifically 1:1, 1:2, 1:3 or 1:4. In the present invention, the molar ratio of 2,2,2-trifluoroethyl acrylate and perfluorohexylethyl acrylate in the mixture of 2,2,2-trifluoroethyl acrylate and perfluorohexylethyl acrylate is preferably 1:1 to 1:4, more preferably 1:1, specifically 1:1, 1:2, 1:3 or 1:4. In the present invention, in the mixture of 2,2,2-trifluoroethyl acrylate, 2-(perfluorobutyl)ethyl methacrylate and perfluorohexylethyl acrylate, the ratio of the amount of 2,2,2-trifluoroethyl acrylate, 2-(perfluorobutyl)ethyl methacrylate and perfluorohexylethyl acrylate is preferably 1:1:1. In the present invention, the polymer monomers are all fluorine-containing substances, so that the fluorine content in the finally formed bicontinuous eutectic electrolyte is high, which can protect the bicontinuous eutectic electrolyte and stabilize the electrode-electrolyte interface, so that the battery using the bicontinuous eutectic electrolyte has excellent long-cycle stability.
[0039] In the present invention, based on the total volume of the deep eutectic electrolyte and the polymer monomer as 100%, the volume content of the polymer monomer is preferably 10-60%, more preferably 20-50%, specifically 10%, 20%, 30%, 40%, 50% or 60%.
[0040] The raw materials for preparing the bicontinuous eutectic electrolyte provided by the present invention include a crosslinking agent, and the crosslinking agent is preferably poly (ethylene glycol) diacrylate. In the present invention, the amount of the crosslinking agent accounts for 0.2-5% of the amount of the polymer monomer, and is further preferably 1-3%, and can be specifically 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%.
[0041] The raw materials for preparing the bicontinuous eutectic electrolyte provided by the present invention include an initiator, and the initiator preferably includes azobisisobutyronitrile (AIBN) and / or dibenzoyl peroxide (BPO), and more preferably azobisisobutyronitrile (AIBN) or dibenzoyl peroxide (BPO). In the present invention, the mass of the initiator and the amount ratio of the total volume of the deep eutectic electrolyte and the polymer monomer are preferably 0.1 to 1 mg / mL, and more preferably 0.2 to 0.5 mg / mL, and specifically can be 0.1 mg / mL, 0.2 mg / mL, 0.25 mg / mL, 0.3 mg / mL, 0.4 mg / mL, 0.5 mg / mL, 0.6 mg / mL, 0.7 mg / mL, 0.8 mg / mL, 0.9 mg / mL or 1 mg / mL.
[0042] The present invention also provides a method for preparing the bicontinuous eutectic electrolyte described in the above technical solution, comprising the following steps:
[0043] mixing a polymer monomer and a cross-linking agent to obtain a polymer precursor solution;
[0044] dissolving the initiator with a portion of the deep eutectic electrolyte to obtain an initiator solution;
[0045] During the battery assembly process, the polymer precursor solution, the initiator solution and the remaining deep eutectic electrolyte are mixed, and in-situ free radical polymerization is carried out under thermal initiation conditions to obtain the bicontinuous eutectic electrolyte.
[0046] The present invention mixes polymer monomers and cross-linking agents to obtain a polymer precursor solution.
[0047] In the present invention, the polymer monomer is preferably dried before use, and the drying agent is preferably a molecular sieve.
[0048] The present invention dissolves the initiator with a part of the deep eutectic electrolyte to obtain an initiator solution.
[0049] The present invention does not specifically limit the dissolving method.
[0050] After obtaining the polymer precursor solution and the initiator solution, the present invention mixes the polymer precursor solution, the initiator solution and the remaining deep eutectic electrolyte during the battery assembly process, and performs in-situ free radical polymerization under thermal initiation conditions to obtain the bicontinuous eutectic electrolyte.
[0051] In the present invention, the volume ratio of the partial deep eutectic electrolyte to the remaining deep eutectic electrolyte is preferably 1:1.
[0052] After the mixing, the present invention preferably further comprises standing, and the standing time is preferably 0.5 to 2 hours.
[0053] In the present invention, the temperature of the in-situ free radical polymerization is preferably 40 to 100°C, more preferably 60 to 80°C, specifically 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C; the time is preferably 2 to 30h, more preferably 6 to 24h, more preferably 12 to 18h, specifically 2h, 6h, 12h, 18h, 24h or 30h. In the present invention, the in-situ free radical polymerization is preferably carried out in an oven.
[0054] The present invention also provides the use of the bicontinuous eutectic electrolyte described in the above technical solution or the bicontinuous eutectic electrolyte prepared by the preparation method described in the above technical solution in a lithium ion battery.
[0055] In the present invention, when the bicontinuous eutectic electrolyte is applied to a lithium ion battery, it is preferably used as an electrolyte of the lithium ion battery. In the present invention, the negative electrode of the lithium ion battery is preferably a lithium sheet, and the positive electrode of the lithium ion battery is preferably lithium iron phosphate (LFP).
[0056] The present invention does not specifically limit the application mode of the bicontinuous eutectic electrolyte, and those skilled in the art may configure it according to actual needs.
[0057] The bicontinuous eutectic electrolyte provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0058] Example 1
[0059] S1. Preparation of deep eutectic electrolyte
[0060] In a glove box (argon protection, H2O, O2 <0.1ppm), 1mmol LiTFSI and 4mmol 1,3-dimethyl-2-imidazolidinone (DMI) were weighed into a 10mL sample bottle and placed on a heating table. They were heated at 50°C for eutectic formation. After all the solid substances were converted into liquid substances, the solution was allowed to stand to obtain a deep eutectic electrolyte.
[0061] S2. Preparation of polymer precursor solution
[0062] Weigh 1mmol of 2,2,2-trifluoroethyl acrylate and 1mmol of 2-(perfluorobutyl)ethyl methacrylate into a sample bottle and dry them with molecular sieves. At room temperature, mix the dried monomers in a 1:1 ratio, and slowly add a 1% molar fraction of poly(ethylene glycol) diacrylate macromolecular crosslinker to obtain a polymer precursor solution. At the same time, dissolve 1mg of initiator azobisisobutyronitrile (AIBN) in the deep eutectic electrolyte obtained by 1mL S1 to obtain an initiator solution for use.
[0063] S3. Preparation of bicontinuous eutectic electrolyte
[0064] The deep eutectic electrolyte prepared in S1, the polymer precursor solution prepared in S2, and the initiator solution prepared in S2 were mixed at a volume ratio of 0.5:1:0.5, and allowed to stand at room temperature for 2 hours. The battery was assembled using commercial lithium iron phosphate LFP electrode sheets and lithium metal electrode sheets as the electrode sheets (non-woven fabrics or glass fibers were used to prevent the positive and negative electrodes from contacting). After the battery was assembled, it was placed in an oven at 60°C for in-situ free radical polymerization for 12 hours to obtain a bicontinuous eutectic electrolyte.
[0065] Figure 1 This is a SEM image of the bicontinuous eutectic electrolyte obtained in Example 1. Figure 1 The upper row of pictures are SEM pictures of the cross section of the bicontinuous eutectic electrolyte at different magnifications, and the lower row of pictures are SEM pictures of the surface of the bicontinuous eutectic electrolyte at different magnifications. Figure 1 It can be seen that the bicontinuous eutectic electrolyte obtained in Example 1 has a clear bicontinuous structure.
[0066] Figure 2 The AC impedance diagram of the bicontinuous eutectic electrolyte obtained in Example 1 at different temperatures is shown in FIG. Figure 2 It can be seen that the bicontinuous eutectic electrolyte obtained in Example 1 has a relatively low interface impedance, specifically, the interface impedance is about 140Ω at room temperature.
[0067] Figure 3 The ionic conductivity diagram of the bicontinuous eutectic electrolyte obtained in Example 1 is shown in FIG. Figure 3 It can be seen that the bicontinuous eutectic electrolyte obtained in Example 1 has a high ionic conductivity, exceeding 10 -4 S / cm, specifically 2.10×10 - 4 S / cm.
[0068] Figure 4 is the LSV curve of the bicontinuous eutectic electrolyte obtained in Example 1. Figure 4 It can be seen that the decomposition voltage of the bicontinuous eutectic electrolyte obtained in Example 1 is about 4.5V.
[0069] Figure 5 The long cycle stability diagram of the Li / / Li symmetric battery with the bicontinuous eutectic electrolyte obtained in Example 1 is shown in FIG. Figure 5 It can be seen that the bicontinuous eutectic electrolyte obtained in Example 1 has good ion extraction / insertion performance. -2 It can stably cycle more than 250 times.
[0070] Figure 6 The performance diagram of the lithium metal battery using the commercial LFP as the positive electrode of the bicontinuous eutectic electrolyte obtained in Example 1, wherein the upper figure is the charge and discharge curve of the lithium metal battery at room temperature at 1C, and the lower figure is the long cycle performance diagram of the lithium metal battery. Figure 6 As can be seen from the figure above: LFP / / Li using the obtained bicontinuous eutectic electrolyte has good charge and discharge performance, and the polarization voltage is less than 200mV at room temperature and 1C rate. Figure 6 As can be seen from the figure below, the obtained bicontinuous eutectic electrolyte has good long-cycle performance stability. After 2500 cycles, the capacity retention rate exceeds 70%, and the coulombic efficiency is >99%. The long-cycle stability also indirectly proves that the obtained bicontinuous eutectic electrolyte has excellent mechanical properties.
[0071] Example 2
[0072] S1. Preparation of deep eutectic electrolyte
[0073] In a glove box (argon protection, H2O, O2 <0.1ppm), 1mmol LiTFSI and 4mmol N-methylacetamide (NMA) were weighed into a 10mL sample bottle and placed on a heating table. They were heated at 50°C for eutectic formation. After all the solid substances were converted into liquid substances, the mixture was allowed to stand to obtain a deep eutectic electrolyte.
[0074] S2. Preparation of polymer precursor solution
[0075] Weigh 1mmol of 2,2,2-trifluoroethyl acrylate and 1mmol of 2-(perfluorobutyl)ethyl methacrylate into a sample bottle and dry them with molecular sieves. At room temperature, mix the dried monomers in a 1:1 ratio and slowly add 1% of poly(ethylene glycol) diacrylate macromolecular crosslinker at a molar fraction to obtain a polymer precursor solution. At the same time, dissolve 1mg of initiator azobisisobutyronitrile (AIBN) in 1mL of deep eutectic electrolyte prepared by S1 to obtain an initiator solution for use.
[0076] S3. Preparation of bicontinuous eutectic electrolyte
[0077] The deep eutectic electrolyte prepared in S1, the polymer precursor solution prepared in S2, and the initiator solution prepared in S2 were mixed at a volume ratio of 0.5:1:0.5, and allowed to stand at room temperature for 2 hours. The battery was assembled using commercial lithium iron phosphate LFP electrode sheets and lithium metal electrode sheets as the electrode sheets (non-woven fabrics or glass fibers were used to prevent the positive and negative electrodes from contacting). After the battery was assembled, it was placed in an oven at 60°C for in-situ free radical polymerization for 12 hours to obtain a bicontinuous eutectic electrolyte.
[0078] The obtained bicontinuous eutectic electrolyte was tested according to the method of Example 1. The results showed that the interface impedance at room temperature was about 160Ω, and the ionic conductivity at room temperature was 1.87×10 -4 S / cm, the decomposition voltage is 4.3V, and the current density is 0.1mA / cm -2 The lower symmetrical battery can stably cycle for more than 300 cycles, and the LFP / / Li battery can stably cycle for 500 cycles, with a capacity retention rate of more than 70% and a coulombic efficiency of >98%.
[0079] Example 3
[0080] S1. Preparation of deep eutectic electrolyte
[0081] In a glove box (argon protection, H2O, O2 <0.1ppm), 1mmol LiTFSI and 4mmol N-methylurea (NML) were weighed into a 10mL sample bottle and placed on a heating table. They were heated at 50°C for eutectic formation. After all the solid substances were converted into liquid substances, the mixture was allowed to stand to obtain a deep eutectic electrolyte.
[0082] S2. Preparation of polymer precursor solution
[0083] Weigh 1mmol of 2,2,2-trifluoroethyl acrylate and 1mmol of 2-(perfluorobutyl)ethyl methacrylate into a sample bottle and dry them with molecular sieves; at room temperature, mix the dried monomers in a 1:1 ratio, and slowly add 1% of poly(ethylene glycol) diacrylate macromolecular crosslinker at a molar fraction to obtain a deep eutectic electrolyte. At the same time, dissolve 1mg of initiator azobisisobutyronitrile (AIBN) in the deep eutectic electrolyte prepared with 1mL S1 to obtain an initiator solution for use.
[0084] S3. Preparation of bicontinuous eutectic electrolyte
[0085] The deep eutectic electrolyte prepared in S1, the polymer precursor solution prepared in S2, and the initiator solution prepared in S2 were mixed at a volume ratio of 0.5:1:0.5, and allowed to stand at room temperature for 2 hours. The battery was assembled using commercial lithium iron phosphate LFP electrode sheets and lithium metal electrode sheets as the electrode sheets (non-woven fabrics or glass fibers were used to prevent the positive and negative electrodes from contacting). After the battery was assembled, it was placed in an oven at 60°C for in-situ free radical polymerization for 12 hours to obtain a bicontinuous eutectic electrolyte.
[0086] The obtained bicontinuous eutectic electrolyte was tested according to the method of Example 1. The results showed that the interface impedance at room temperature was about 176Ω, and the ionic conductivity at room temperature was 1.69×10 -4 S / cm, the decomposition voltage is 4.4V, and the current density is 0.1mA / cm -2The lower symmetrical battery can stably cycle for more than 200 cycles, and the LFP / / Li battery can stably cycle for 600 cycles, with a capacity retention rate of more than 70% and a coulombic efficiency of >98%.
[0087] Example 4
[0088] S1. Preparation of deep eutectic electrolyte
[0089] In a glove box (argon protection, H2O, O2 <0.1ppm), 1mmol LiTFSI and 4mmol N-methyl-2,2,2-trifluoroacetamide (NMF) were weighed into a 10mL sample bottle and placed on a heating table. They were heated at 50°C for eutectic formation. After all the solid substances were converted into liquid substances, the mixture was allowed to stand to obtain a deep eutectic electrolyte.
[0090] S2. Preparation of polymer precursor solution
[0091] Weigh 1mmol of 2,2,2-trifluoroethyl acrylate and 1mmol of 2-(perfluorobutyl)ethyl methacrylate into a sample bottle and dry them with molecular sieves; at room temperature, mix the dried monomers in a 1:1 ratio, and slowly add 1% of poly(ethylene glycol) diacrylate macromolecular crosslinker at a molar fraction to obtain a polymer precursor solution. At the same time, dissolve 1mg of initiator azobisisobutyronitrile (AIBN) in 1mL of deep eutectic electrolyte prepared by S1 to obtain an initiator solution for use.
[0092] S3. Preparation of bicontinuous eutectic electrolyte
[0093] The deep eutectic electrolyte prepared in S1, the polymer precursor solution prepared in S2, and the initiator solution prepared in S2 were mixed at a volume ratio of 0.5:1:0.5, and allowed to stand at room temperature for 2 hours. The battery was assembled using commercial lithium iron phosphate LFP electrode sheets and lithium metal electrode sheets as the electrode sheets (non-woven fabrics or glass fibers were used to prevent the positive and negative electrodes from contacting). After the battery was assembled, it was placed in an oven at 60°C for in-situ free radical polymerization for 12 hours to obtain a bicontinuous eutectic electrolyte.
[0094] The obtained bicontinuous eutectic electrolyte was tested according to the method of Example 1. The results showed that the interface impedance at room temperature was about 149Ω, and the ionic conductivity at room temperature was 2.01×10 -4 S / cm, the decomposition voltage is 4.4V, and the current density is 0.1mA / cm -2 The lower symmetrical battery can stably cycle for more than 200 cycles, and the LFP / / Li battery can stably cycle for 600 cycles, with a capacity retention rate of more than 80% and a coulombic efficiency of >99%.
[0095] Example 5
[0096] S1. Preparation of deep eutectic electrolyte
[0097] In a glove box (argon protection, H2O, O2 <0.1ppm), 1mmol LiTFSI and 4mmol cyclopentane sulfone were weighed into a 10mL sample bottle and placed on a heating table. They were heated at 50°C for eutectic formation. After all the solid substances were converted into liquid substances, they were allowed to stand to obtain a deep eutectic electrolyte.
[0098] S2. Preparation of polymer precursor solution
[0099] Weigh 1mmol of 2,2,2-trifluoroethyl acrylate and 1mmol of 2-(perfluorobutyl)ethyl methacrylate into a sample bottle and dry them with molecular sieves. At room temperature, mix the dried monomers in a 1:1 ratio and slowly add 1% of poly(ethylene glycol) diacrylate macromolecular crosslinker at a molar fraction to obtain a polymer precursor solution. At the same time, dissolve 1mg of initiator azobisisobutyronitrile (AIBN) in 1mL of deep eutectic electrolyte prepared by S1 to obtain an initiator solution for use.
[0100] S3. Preparation of bicontinuous eutectic electrolyte
[0101] The deep eutectic electrolyte prepared in S1, the polymer precursor solution prepared in S2, and the initiator solution prepared in S2 were mixed at a volume ratio of 0.5:1:0.5. After standing at room temperature for 2 hours, the battery was assembled using commercial lithium iron phosphate LFP electrode sheets and lithium metal electrode sheets as the electrode sheets (non-woven fabrics or glass fibers were used to prevent contact between the positive and negative electrodes). After the battery was assembled, it was placed in an oven at 60°C for in-situ free radical polymerization for 12 hours to obtain a bicontinuous eutectic electrolyte.
[0102] The obtained bicontinuous eutectic electrolyte was tested according to the method of Example 1. The results showed that the interface impedance at room temperature was about 210Ω, and the ionic conductivity at room temperature was 1.42×10 -4 S / cm, the decomposition voltage is 4.7V, and the current density is 0.1mA / cm -2 The lower symmetrical battery can stably cycle for more than 400 cycles, and the LFP / / Li battery can stably cycle for 400 cycles, with a capacity retention rate of more than 80% and a coulombic efficiency of >99%.
[0103] Example 6
[0104] S1. Preparation of deep eutectic electrolyte
[0105] In a glove box (argon protection, H2O, O2 <0.1ppm), 1mmol LiTFSI and 4mmol 1,3-dimethyl-2-imidazolidinone (DMI) were weighed into a 10mL sample bottle and placed on a heating table. They were heated at 50°C for eutectic formation. After all the solid substances were converted into liquid substances, the solution was allowed to stand to obtain a deep eutectic electrolyte.
[0106] S2. Preparation of polymer precursor solution
[0107] Weigh 1mmol of 2,2,2-trifluoroethyl acrylate and 1mmol of perfluorohexyl ethyl acrylate into a sample bottle and dry them with molecular sieves. At room temperature, mix the dried monomers in a 1:1 ratio, and slowly add a 1% molar fraction of poly(ethylene glycol) diacrylate macromolecular crosslinker to obtain a polymer precursor solution. At the same time, dissolve 1mg of initiator azobisisobutyronitrile (AIBN) in 1mL of deep eutectic electrolyte prepared by S1 to obtain an initiator solution for use.
[0108] S3. Preparation of bicontinuous eutectic electrolyte
[0109] The deep eutectic electrolyte prepared in S1, the polymer precursor solution prepared in S2, and the initiator solution prepared in S2 were mixed at a volume ratio of 0.5:1:0.5, and allowed to stand at room temperature for 2 hours, and the battery was assembled using commercial lithium iron phosphate LFP electrode sheets and lithium metal electrode sheets as the electrode sheets (non-woven fabrics or glass fibers were used to prevent the positive and negative electrodes from contacting). After the battery was assembled, it was placed in an oven at 60°C for in-situ free radical polymerization for 12 hours to obtain the bicontinuous eutectic electrolyte.
[0110] The obtained bicontinuous eutectic electrolyte was tested according to the method of Example 1. The results showed that the interface impedance at room temperature was about 152Ω, and the ionic conductivity at room temperature was 1.97×10 -4 S / cm, the decomposition voltage is 4.5V, and the current density is 0.1mA / cm -2 The lower symmetrical battery can stably cycle for more than 400 cycles, and the LFP / / Li battery can stably cycle for 800 cycles, with a capacity retention rate of more than 70% and a coulombic efficiency of >98%.
[0111] Example 7
[0112] S1. Preparation of deep eutectic electrolyte
[0113] In a glove box (argon protection, H2O, O2 <0.1ppm), 1mmol LiTFSI and 4mmol 1,3-dimethyl-2-imidazolidinone (DMI) were weighed into a 10mL sample bottle and placed on a heating table. They were heated at 50°C for eutectic formation. After all the solid substances were converted into liquid substances, the solution was allowed to stand to obtain a deep eutectic electrolyte.
[0114] S2. Preparation of polymer precursor solution
[0115] Weigh 1mmol of 2,2,2-trifluoroethyl acrylate and 4mmol of 2-(perfluorobutyl)ethyl methacrylate into a sample bottle and dry with molecular sieves. At room temperature, mix the dried monomers in a ratio of 4:1, and slowly add a 1% molar fraction of poly(ethylene glycol) diacrylate macromolecular crosslinker to obtain a polymer precursor solution. At the same time, dissolve 1mg of initiator azobisisobutyronitrile (AIBN) in 1mL of deep eutectic electrolyte prepared by S1 to obtain an initiator solution for use.
[0116] S3. Preparation of bicontinuous eutectic electrolyte
[0117] The eutectic electrolyte prepared in S1, the polymer precursor solution prepared in S2, and the initiator solution prepared in S2 were mixed at a volume ratio of 0.5:1:0.5, and allowed to stand at room temperature for 2 hours. Commercial lithium iron phosphate LFP electrode sheets and lithium metal electrode sheets were used as electrode sheets (non-woven fabrics or glass fibers were used to prevent contact between the positive and negative electrodes) for battery assembly. After the battery was assembled, it was placed in an oven at 60°C for in-situ free radical polymerization for 12 hours to obtain a bicontinuous eutectic electrolyte.
[0118] The obtained bicontinuous eutectic electrolyte was tested according to the method of Example 1. The results showed that the interface impedance at room temperature was about 120Ω, and the ionic conductivity at room temperature was 2.52×10 -4 S / cm, the decomposition voltage is 4.5V, and the current density is 0.1mA / cm -2 The lower symmetrical battery can stably cycle for more than 200 cycles, and the LFP / / Li battery can stably cycle for 700 cycles, with a capacity retention rate of more than 70% and a coulombic efficiency of >99%.
[0119] Example 8
[0120] S1. Preparation of deep eutectic electrolyte
[0121] In a glove box (argon protection, H2O, O2 <0.1ppm), 1mmol LiTFSI and 4mmol 1,3-dimethyl-2-imidazolidinone (DMI) were weighed into a 10mL sample bottle and placed on a heating table. They were heated at 50°C for eutectic formation. After all the solid substances were converted into liquid substances, the solution was allowed to stand to obtain a deep eutectic electrolyte.
[0122] S2. Preparation of polymer precursor solution
[0123] Weigh 1 mmol of 2,2,2-trifluoroethyl acrylate and 1 mmol of 2-(perfluorobutyl)ethyl methacrylate into a sample bottle and dry them with molecular sieves. At room temperature, mix the dried monomers in a 1:1 ratio and slowly add a 1% molar fraction of poly(ethylene glycol) diacrylate macromolecular crosslinker to obtain a polymer precursor solution. At the same time, dissolve 1 mg of initiator dibenzoyl peroxide (BPO) in 1 mL of the deep eutectic electrolyte prepared by S1 to obtain an initiator solution for use.
[0124] S3. Preparation of bicontinuous eutectic electrolyte
[0125] The deep eutectic electrolyte prepared in S1, the polymer precursor solution prepared in S2, and the initiator solution prepared in S2 were mixed at a volume ratio of 0.5:1:0.5, and allowed to stand at room temperature for 2 hours. The battery was assembled using commercial lithium iron phosphate LFP electrode sheets and lithium metal electrode sheets as the electrode sheets (non-woven fabrics or glass fibers were used to prevent the positive and negative electrodes from contacting). After the battery was assembled, it was placed in an oven at 60°C for in-situ free radical polymerization for 12 hours to obtain a bicontinuous eutectic electrolyte.
[0126] The obtained bicontinuous eutectic electrolyte was tested according to the method of Example 1. The results showed that the interface impedance at room temperature was about 166Ω, and the ionic conductivity at room temperature was 1.81×10 -4 S / cm, the decomposition voltage is 4.4V, and the current density is 0.1mA / cm -2 The lower symmetrical battery can stably cycle for more than 300 cycles, and the LFP / / Li battery can stably cycle for 800 cycles, with a capacity retention rate of more than 70% and a coulombic efficiency of >98%.
[0127] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A bicontinuous eutectic electrolyte, the raw materials for preparation comprising: Deep eutectic electrolytes, polymer monomers, crosslinkers, and initiators; The polymer monomers are at least two of 2,2,2-trifluoroethyl acrylate, 2-(perfluorobutyl)ethyl methacrylate and perfluorohexylethyl acrylate; The bicontinuous eutectic electrolyte has a microscopic bicontinuous phase separation structure.
2. The bicontinuous eutectic electrolyte according to claim 1, characterized in that: The phase separation size in the microscopic bicontinuous phase separation structure is 10 nm to 10 μm.
3. The bicontinuous eutectic electrolyte according to claim 1, characterized in that: The deep eutectic electrolyte is prepared by eutecticizing a ligand and an electrolyte salt, wherein the molar ratio of the ligand to the electrolyte salt is 2:1 to 8:1; the ligand is an amide or a sulfone; and the electrolyte salt is lithium bis(trifluoromethanesulfonyl)imide.
4. The bicontinuous eutectic electrolyte according to claim 3, characterized in that: The amides include one or more of 1,3-dimethyl-2-imidazolidinone, N-methylacetamide, N-methyl-2,2,2-trifluoroacetamide and N-methylurea, and the sulfones include one or more of dimethyl sulfone, dibutyl sulfone and cyclopentane sulfone.
5. The bicontinuous eutectic electrolyte according to claim 1, characterized in that: The crosslinking agent is poly(ethylene glycol) diacrylate, and the amount of the crosslinking agent accounts for 0.2-5% of the amount of the polymer monomer.
6. The bicontinuous eutectic electrolyte according to claim 1, characterized in that: The initiator comprises azobisisobutyronitrile and / or dibenzoyl peroxide; the mass of the initiator and the total volume of the deep eutectic electrolyte and the polymer monomer have a usage ratio of 0.1 to 1 mg / mL.
7. The bicontinuous eutectic electrolyte according to claim 1, characterized in that: Taking the total volume of the deep eutectic electrolyte and the polymer monomer as 100%, the volume content of the polymer monomer is 10-60%.
8. The method for preparing a bicontinuous eutectic electrolyte according to any one of claims 1 to 7, characterized in that: The following steps are involved: mixing a polymer monomer and a cross-linking agent to obtain a polymer precursor solution; dissolving the initiator with a portion of the deep eutectic electrolyte to obtain an initiator solution; During the battery assembly process, the polymer precursor solution, the initiator solution and the remaining deep eutectic electrolyte are mixed, and in-situ free radical polymerization is carried out under thermal initiation conditions to obtain the bicontinuous eutectic electrolyte.
9. The preparation method according to claim 8, characterized in that: The temperature of the in-situ free radical polymerization is 40-100° C., and the time is 2-30 hours.
10. Use of the bicontinuous eutectic electrolyte according to any one of claims 1 to 7 or the bicontinuous eutectic electrolyte prepared by the preparation method according to any one of claims 8 to 9 in lithium ion batteries.
Citation Information
Cited By
Polymer and polymer GEL electrolyte
WO2026193544A1